Immunomodulating properties of cyclic dimeric guanozinmonophosphate and its structural analogues - Zafranskaya, Marina M. (Journal of the Belarusian State University. Ecology, 2019)
The results of studying the effects of cyclic dimeric guanosine monophosphate (c-di-GMP) and its structural analogues – cyclic dimeric 2-araguanosine monophosphate (c-di-araGMP) and cyclic dimeric 2-deoxyguanasine monophosphate (c-di-deoxyGMP) on the extra- and intracellular production of tumor necrosis factor alfa, type 1 and type 2 interferons by human peripheral blood mononuclear cells during in vitro non-specific and myelin-specific stimulation are presented in the paper. Cyclic dinucleotides have been established to have a stimulating effect on the production of TNF-α, IFN-α and IFN-γ by mitogen-activated human peripheral blood mononuclear cells with a simultaneous inhibition by c-di-GMP at concentration of 10–4М and 10–5М of extracellular type I and type II interferons during myelin-specific stimulation secretion in vitro. The obtained results open up a broad perspective for developing new drugs aimed at regulating anti-infective immunity and maintaining peripheral tolerance of the immune system in relation to the human organism own antigens, and also demonstrate the need in further research for studying the effects of these compounds in immunopathological conditions.